Psychometric properties of the Women's Eating Disorder Questionnaire - Pawłowska, Beata; Potembska, Emilia (Current Problems of Psychiatry, 2015)
The article presents the successive stages of development of the Women's Eating Disorder Questionnaire (KBZOK). As the first stage, a questionnaire consisting of 64 items was developed This preliminary version of the questionnaire was used to investigate 185 women. The items with weak variation were withdrawn. In the next stage, factor analysis was carried out, on the basis of which four factors (scales) were elicited: (1) Negative body image, (2) Binge eating, (3) Restrictive diets, and (4) Purging. Items with the lowest factor loadings and the lowest factor specificity indexes were rejected. The factors identified explained 63% of the total variance. The final version of the KBZOK questionnaire consisted of 37 items. The coefficients of reliability for the individual factors were Cronbach's alpha = 0.93 for Negative body image, Cronbach's alpha = 0.92 for Binge Eating, Cronbach's alpha = 0.92 for Restrictive diets, and Cronbach's alpha = 0.77 for Purging.